Occupational therapy in oncology palliative care for adolescents and young adults: Perspectives of Australian occupational therapists. (28th December 2021) - Wallis, Amy; Meredith, Pamela; Stanley, Mandy
Abstract: Introduction: Palliative Care Australia suggests current needs (emotional wellbeing, understanding of cancers impact on relationships, everyday activities, and life milestones) for adolescent and young adults in palliative care are unmet due to a lack of age‐specific palliative care facilities in Australia. This includes the provision of occupational therapy that can impact these unmet needs. Although the occupational therapy role in palliative care has been documented, little is known about existing occupational therapy services or occupational needs for young people with palliative care needs. The aims of this study were to obtain occupational therapists insights of working with this population in Australia regarding (1) gaps in palliative care services for this population; (2) facilitators and challenges to providing occupational therapy for this group; and (3) perceived occupational needs of young people living with a life‐limiting cancer diagnosis. Methods: Using snowball sampling, an online survey was distributed to occupational therapists with experience working in palliative cancer care with adolescents and young adults. Available for 6 weeks, the survey included demographic, work history, and service delivery questions. Forced‐choice questions were summarised descriptively, and content analysis was used to analyse free‐text data. Results: Eleven completed surveys were returned. Overall, therapists perceived current palliative care services for this population within Australia to be lacking. Two gaps emerged: age‐appropriate facilities and gaps in provision of psycho‐social and occupational therapy services. Funding, lack of knowledge of the occupational therapy role, and professional confidence were highlighted as challenges to practice. Main occupational needs related to maintenance of as "normal" a life as possible: maintaining occupational role engagement, continuing connection with others, and being heard regarding their occupational needs. Conclusion: Findings suggest a need for service changes, including custom‐designed facilities, improved funding, training and mentoring, to support age‐appropriate and occupation‐focussed care for the young person in cancer‐specific palliative care.